To factor the given binomials using the difference of squares, we can use the formula:
\[ a^2 - b^2 = (a - b)(a + b) \]
We will apply this to each binomial that represents a difference of squares.
-
For \( 4x^2 - 36 \):
Here, \( a^2 = 4x^2 \) and \( b^2 = 36 \).
- \( a = 2x \)
- \( b = 6 \)
Thus, it factors as: \[ 4x^2 - 36 = (2x - 6)(2x + 6) \]
-
For \( 9x^2 - 25 \):
Here, \( a^2 = 9x^2 \) and \( b^2 = 25 \).
- \( a = 3x \)
- \( b = 5 \)
Thus, it factors as: \[ 9x^2 - 25 = (3x - 5)(3x + 5) \]
-
For \( 9 - 25x^2 \):
We can rearrange it to \( - (25x^2 - 9) \), which gives us a difference of squares. Here, \( a^2 = 9 \) and \( b^2 = 25x^2 \).
- \( a = 3 \)
- \( b = 5x \)
Thus, it factors as: \[ 9 - 25x^2 = -(25x^2 - 9) = (3 - 5x)(3 + 5x) \]
-
For \( 81x^2 - 49 \):
Here, \( a^2 = 81x^2 \) and \( b^2 = 49 \).
- \( a = 9x \)
- \( b = 7 \)
Thus, it factors as: \[ 81x^2 - 49 = (9x - 7)(9x + 7) \]
-
For \( 4x^2 + 36 \):
This expression is not a difference of squares; it represents a sum of squares and cannot be factored using the difference of squares method.
So, the factored forms of the polynomials using the difference of squares are:
- \( 4x^2 - 36 = (2x - 6)(2x + 6) \)
- \( 9x^2 - 25 = (3x - 5)(3x + 5) \)
- \( 9 - 25x^2 = (3 - 5x)(3 + 5x) \)
- \( 81x^2 - 49 = (9x - 7)(9x + 7) \)
- \( 4x^2 + 36 \) does not factor with this method.